2018
DOI: 10.3390/f9100586
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Cost Spore Trap Allows Collection and Real-Time PCR Quantification of Airborne Fusarium circinatum Spores

Abstract: A variety of commercial instruments are available for sampling and quantifying microscopic airborne organisms from the environment. Although most samplers are highly sensitive, they are also expensive, costing thousands of dollars per unit, a price that is out of reach for many researchers, especially those looking to design experiments with replication. While looking at options to monitor pine stands for the presence of Fusarium circinatum, the causal agent of pitch canker disease, on multiple sites with seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…Other studies have also shown that spores of F. circinatum can be detected throughout the year, either in natural adult Pinus spp. forests (Garbelotto et al, ), plantations (Dvořák et al, ; Quesada et al, ) or pine‐producing seedling nurseries (Fourie et al, ). Concerning the spore dispersal distance, our results show that inoculum detection was higher at the centre of the plots, significantly dropping at the edge, and closer to zero outside.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have also shown that spores of F. circinatum can be detected throughout the year, either in natural adult Pinus spp. forests (Garbelotto et al, ), plantations (Dvořák et al, ; Quesada et al, ) or pine‐producing seedling nurseries (Fourie et al, ). Concerning the spore dispersal distance, our results show that inoculum detection was higher at the centre of the plots, significantly dropping at the edge, and closer to zero outside.…”
Section: Discussionmentioning
confidence: 99%
“…Trapping of aerial spores of F. circinatum has been performed successfully elsewhere, either by passive (Fourie et al, 2014;Garbelotto et al, 2007) or active (Dvořák et al, 2017;Quesada et al, 2018) traps. In this work, a variant of the passive filter method developed by Schweigkofler et al (2004) was used to trap the aerial F I G U R E 3 (a) Proportion of positive spore traps for Fusarium circinatum by plot, location and date in 2015.…”
Section: Discussionmentioning
confidence: 99%
“…The same approach was used in South Africa by Fourie et al [44], who measured spore deposition rates within a commercial seedling nursery. Most recently, Quesada et al [45] developed a new low-cost spore trap for collecting F. circinatum spores, based on a rotating motor that holds a metal rod and two petroleum jelly-coated microscope slides, which they also subjected to the quantification using the method of Schweigkofler et al [43] Samples collected in such a way are most likely to yield the fungus, as indicated by Martínez-Álvarez et al [39]. These authors demonstrated that the relative isolation frequency was highest when the sample was collected from a canker in the trunk.…”
Section: Spore Trappingmentioning
confidence: 99%
“…The same approach was used in South Africa by Fourie et al [44], who measured spore deposition rates within a commercial seedling nursery. Most recently, Quesada et al [45] developed a new low-cost spore trap for collecting F. circinatum spores, based on a rotating motor that holds a metal rod and two petroleum jelly-coated microscope slides, which they also subjected to the quantification using the method of Schweigkofler et al [43].…”
Section: Spore Trappingmentioning
confidence: 99%
“…For two weeks prior to collecting the above samples, we also deployed an air sampler modified from Quesada et al [39] at each of our H. tiliaceus sites, which collected aerial microbes on rotating sterilized glass slides lined with microtiter plate sealing film (Thermo Fisher Scientific, Waltham, MA). We immediately transferred all swabs and film to a microcentrifuge tube with 1 mL lysis buffer and garnet homogenization beads (Qiagen NV, Venlo, Netherlands; see Supplementary Methods for details).…”
Section: Site Description and Samplingmentioning
confidence: 99%